Light‐Driven Liquid Crystalline Networks and Soft Actuators with Degree‐of‐Freedom‐Controlled Molecular Motors. (12th March 2020) - Lan, Ruochen; Sun, Jian; Shen, Chen; Huang, Rui; Zhang, Zhongping; Ma, Cong; Bao, Jinying; Zhang, Lanying; Wang, Ling; Yang, Dengke; Yang, Huai
Abstract: Design and fabrication of photomechanical soft actuators has attracted intense scientific interest because of their potential in the manufacture of untethered intelligent soft robots and advanced functional devices. Trifunctional and monofunctional polymerizable molecular motors are judiciously designed and synthesized. Novel light‐driven liquid crystalline networks (LCN) are prepared by crosslinking overcrowded‐alkene‐based molecular motors with different degrees of freedom into the anisotropic LCN. The photoisomerization and thermal helix inversion of light‐driven molecular motors are reversible when only the upper part of the molecular motor is linked to the network, endowing the LCN film with remarkable photoactive performance. However, photochemical geometric change of the light‐driven molecular motor does not work after crosslinking both the upper and lower part of the motor by polymer chains. Interestingly, it is found that the fastened motor can transfer the light energy into localized heat instead of performing photoisomerization. The light‐driven molecular‐motor‐based LCN soft actuators are demonstrated to function as a grasping hand, where the continuous motions of grasping, moving, lifting, and releasing an object are successfully achieved. This work may provide inspiration to the preparation of next‐generation photoactive advanced functional materials toward their wide applications in the areas of photonics, optoelectronics, soft robotics, and beyond. Abstract : An overcrowded‐alkene‐based molecular motor (MM) is chemically crosslinked into a liquid crystalline network (LCN). In contrast to a monofunctional MM, which exhibits photoisomerization after crosslinking in LCN, the trifunctional MM cannot isomerize under light irradiation because of the restriction of the network but transfers the incident photon energy into heat, allowing the LCN to perform remarkable photo‐controllable motion through photothermal effects.